2021
DOI: 10.3390/toxins13030213
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum Toxin A and Osteosarcopenia in Experimental Animals: A Scoping Review

Abstract: We conducted a scoping review to investigate the effects of intramuscular injection of Botulinum Toxin A (BoNT-A) on bone morphology. We investigated if the muscle atrophy associated with Injection of BoNT-A had effects on the neighboring bone. We used the search terms: osteopenia, bone atrophy, Botulinum Toxin A, Micro-CT, mice or rat. The following databases were searched: Medline, Embase, PubMed and the Cochrane Library, between 1990 and 2020. After removal of duplicates, 228 abstracts were identified of wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…In preclinical studies, BTX injections in hindlimbs are an established experimental animal model to study disuse-induced bone loss. 14,15 To maintain healthy bones, mechanical loads from muscular contraction and gravitational forces are required. The forces falling on bone are sensed by cells known as osteocytes that signal other bone cells including osteoblasts and osteoclasts to form and resorb bone, respectively, maintaining a steady state of bone remodelling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In preclinical studies, BTX injections in hindlimbs are an established experimental animal model to study disuse-induced bone loss. 14,15 To maintain healthy bones, mechanical loads from muscular contraction and gravitational forces are required. The forces falling on bone are sensed by cells known as osteocytes that signal other bone cells including osteoblasts and osteoclasts to form and resorb bone, respectively, maintaining a steady state of bone remodelling.…”
Section: Introductionmentioning
confidence: 99%
“…In preclinical studies, BTX injections in hindlimbs are an established experimental animal model to study disuse‐induced bone loss 14,15 . To maintain healthy bones, mechanical loads from muscular contraction and gravitational forces are required.…”
Section: Introductionmentioning
confidence: 99%
“…21 A scoping review by Tang et al showed all rats and mice injected with an average dose of 20 U/kg presented with significant changes in bony density, architecture and strength. Additionally, Tang et al 22 noted a rapid increase in osteoclasts, downregulation of genes related to bone formation and upregulation of genes related to bone resorption after BoNTA injection.…”
mentioning
confidence: 99%